Daily home monitoring of potassium, creatinine, and estimated plasma volume in heart failure post‐discharge - Patrick Rossignol; Renaud Fay; Nicolas Girerd; Faiez Zannad (ESC Heart Failure)
Abstract Aims Congestive status, serum potassium, and renal function are major determinants of outcomes as well as critical elements for adjusting drug therapy in heart failure (HF) patients. This study aimed at describing the daily variations in estimated plasma volume (ePV, a surrogate of congestion computed from haemoglobin and haematocrit), blood potassium, and estimated glomerular filtration rate during 2 months post‐hospitalization for decompensated HF with reduced ejection fraction. Methods and results The study was conducted in a single tertiary referral centre. Capillary blood samples were drawn by study nurses at home (7–12 am), and haematocrit, blood haemoglobin, creatinine, and potassium were measured using an approved home‐based device (ABOTT i‐STAT) (ClinicalTrials.gov: NCT01655134). Among the 15 home‐monitored patients, two patients died (one suddenly), and one was readmitted for ischaemic acute pulmonary oedema, with a subsequent acute coronary syndrome, and did not have a complete 2‐month follow‐up. The 5‐day‐a‐week biological home monitoring revealed an ePV >5.5 mL/g Hb, suggestive of undiagnosed residual congestion at discharge in 3 out the 15 patients. It was possible to document a number of episodes of hyperkalaemia (>5: mean ± standard deviation: 2.2 ± 2.2 or 5.5: 1.7 ± 1.6 mmol/L), hypokalaemia (<4: 1.9 ± 2.4 or 3.5: 0.5 ± 1.2 mmol/L), worsening renal function (drop in estimated glomerular filtration rate > 20%: 1.3 ± 1.8 or 30%: 0.7 ± 1.2) and recongestion (ePV rise above 10%: 1.4 ± 1.5, 15%: 2.3 ± 2.4, 5.5 mL/g Hb: 1.8 ± 2.6) episodes indicative of clinically relevant and potentially actionable cardiorenal and electrolytic patterns. Conclusions Our findings demonstrate that a 5‐day‐a‐week home monitoring combining haemoglobin/haematocrit, potassium, and creatinine measurements was able to capture a substantial number of clinically relevant cardiorenal and electrolyte events which are frequently overlooked and potentially actionable. Whether acting on these events may help optimizing renin angiotensin aldosterone system inhibitors and diuretic therapy warrants further dedicated testing. The ongoing HERMES HF study (NCT04050904) is assessing the short‐term feasibility and safety of such a monitoring strategy, complemented by a decision support system, and generating recommendations based on ESC clinical guidelines in patients discharged after an episode of worsening heart failure with reduced ejection fraction.